Haematogenous Spread of Staphylococcus aureus from an Iliacus Abscess to an ACL Reconstructed Knee - Vivek Eranki; Andrew Wallis; Simon Smith (Case Reports in Orthopedics)
We describe a case of a 19-year-old male who presented to the South West Health Service with a septic knee, secondary to haematogenous spread from an iliacus abscess. Thus far, there have been no reported cases of haematogenous spread of infection from an iliacus abscess to an ACL reconstructed knee, let alone in a healthy young person with no risk factors. The patient has had several washouts of the knee along with the drainage of the abscess. The ACL graft was saved with the patient making a complete recovery.